La identificación de los sujetos nulos en el español no nativo. - Fernandez de Moya, Zara. (University of Ottawa (Canada), 1996)
The research of this thesis was completed within the framework Chomskian's Principles and Parameters model of acquisition. A detailed analysis of individual production of null-subjects and pronouns in non-native Spanish speakers was carried out in order to determine its relationship with verbal morphology. The fact that the production data available to us for this thesis is part of the investigation project "Classroom Second Language Acquisition: Beyond Parameters," directed by the professor Juana Munoz Liceras, and that this study is a longitudinal analysis of the acquisition of Spanish by children, adolescents and adults, within an institutional context, has enabled us to observe, among other points of interest, variables such as L1 (English or French) and other L2 languages (Arabic, Greek, Portuguese and Italian) as well as taking into consideration the differences relative to age. Finally, and thanks to the empirical data--which the above mentioned study has provided--, a part of this thesis has been dedicated to the analysis of the variability of the IL with respect to the technique of procurement of data elicitation techniques used by the researchers. Hence, we have studied whether the identification procedure in our French, English and bilingual subjects, takes into account the Spanish morphology, or, on the contrary, whether the mother tongue mechanisms of recoverability are maintained.
Keywords: Language, Linguistics.